Some updates to the method for calculation of parameters of bottom trawl system - Egor A. Zakharov; Oleg N. Kruchinin (Известия ТИНРО, 2016)
The method for calculation of geometric parameters of trawl system proposed by F.I. Baranov is analyzed. The calculation includes evaluation of spacer force and drag for all elements of trawl system and solution of transcendental equation to find a distance between the otter boards of bottom trawl. Special attention is paid to considering and enhancement of common techniques for determining force and geometric parameters of some elements of trawl system, with identifying the most appropriate ways. The calculations and experimental data are compared for a trawl system using the Scanmar equipment for monitoring of fishing gear. The updated model simulates more adequately the forming of bottom trawl geometry, therefore it can be used for assessment of the catch area during trawl surveys conducted by bottom trawls.